Inhibitory effects of sesquiterpene lactones from the Indonesian marine sponge Lamellodysidea cf. herbacea on bone morphogenetic protein-induced osteoblastic differentiation. (1st March 2021) - Ohte, Satoshi; Yamazaki, Hiroyuki; Takahashi, Ohgi; Rotinsulu, Henki; Wewengkang, Defny S.; Sumilat, Deiske A.; Abdjul, Delfly B.; Maarisit, Wilmar; Kapojos, Magie M.; Zhang, Huiping; Hayashi, Fumiaki; Namikoshi, Michio; et al.
Graphical abstract: Abstract: A new unique sesquiterpene lactone, bicyclolamellolactone A (1 ), was isolated together with two known monocyclofarnesol-type sesquiterpenes, lamellolactones A (2 ) and B (3 ), from the Indonesian marine sponge Lamellodysidea sp. (cf. L. herbacea ). The planar structure of 1 was assigned based on its spectroscopic data (1D and 2D NMR, HRESIMS, UV, and IR spectra). The relative and absolute configuration of 1 was determined by comparison of its calculated and experimental electronic circular dichroism spectra in combination with NOESY correlations. Compounds 1 –3 inhibited bone morphogenic protein (BMP)-induced alkaline phosphatase activity in mutant BMP receptor-carrying C2C12 cells with IC50 values of 51, 4.6, and 20 μM, respectively.